Message from the Chief Editor - Editor, Chief (Journal of Technical Education and Training, 2014)
Welcome to all our readers to the December issue of JTET. In this issue we are proud to present to our readers five new articles from our international contributors who have generously shared their research findings on the various aspects of TVET. The first article by Umar et al, discusses the resources required for effective management of workshops in technical colleges. It highlights the challenges faced by workshop managers in ensuring workshop facilities are adequate and up to date for effective training purposes. The second article by Ong reports on the learning approaches often used by adult learners. Knowledge on adult learners is indeed useful to TVET providers as adult learners are often enrolled in TVET institutions. The third article by Jalani and Lai looks at how learning in an electrical engineering program can be enhanced using an innovative approach. Specifically, their research investigated the effect of an example-problem-based learning approach on learning transfer in a circuit theory course. The approach can be easily implemented to courses that are of similar cognitive typology. More on learning approaches, but on a different subject matter, the fourth article by Deba et al, reports on the effects of entrepreneurship education on entrepreneurial skills of undergraduate science, vocational and technical education students. As entrepreneurship education has become an important component of TVET, this article should be of great interest to many practitioners in TVET. Our last article by Shuaibu reports on a study that attempts to relate cultural elements to the development of mathematical thinking among technology education students. Since learning is often culturally situated, this article can create awareness towards potential cultural contribution in cognitive development. We hope that our readers will take the time to look through the current articles and will gain some benefits from them. To all our authors, thank you for making this issue possible and to our reviewers, thank you for helping us in ensuring JTET achieve the high quality that it aims for. We hope everyone; from authors to reviewers will continue to give their strong support to this journal. Last but not least, happy holidays and may everyone have a happy and prosperous New Year of 2015.